2006
DOI: 10.1007/s10565-006-0151-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methanol intoxication on spcific immune functions of albino rats

Abstract: Our previous studies revealed that methanol intoxication significantly altered the non-specific immune functions in albino rats. The present investigation focuses on the effect of methanol on certain specific immune functions of cell mediated immunity such as footpad thickness, leukocyte migration inhibition test (LMI) and antibody levels. In addition, serum interleukins (IL-2, IL-4, TNF-alpha and IFN-gamma), and splenic lymphocyte subsets were measured after an immune challenge. The specific immune function t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
(44 reference statements)
1
8
0
1
Order By: Relevance
“…70 The results of present study seem to suggest that the aspartame metabolite methanol or formaldehyde may be involved in inducing oxidative stress in serum and in changes of cytokine secretion where Th1 cytokines are down-regulated and Th2 cytokines are upregulated, which may alter cell and humoral immunity. This report is strengthened by previous published studies by Parthasarathy et al, 71 where methanol intoxication alters immune function.…”
Section: Discussionsupporting
confidence: 74%
“…70 The results of present study seem to suggest that the aspartame metabolite methanol or formaldehyde may be involved in inducing oxidative stress in serum and in changes of cytokine secretion where Th1 cytokines are down-regulated and Th2 cytokines are upregulated, which may alter cell and humoral immunity. This report is strengthened by previous published studies by Parthasarathy et al, 71 where methanol intoxication alters immune function.…”
Section: Discussionsupporting
confidence: 74%
“…The prediction of the potential immunotoxic effects of the aspartame metabolite methanol based on in vitro studies with thymocytes (Oyama et al 2002, Nakao et al 2003) is highly speculative Although in subsequent in vivo studies by Parthasarathy et al (2006Parthasarathy et al ( , 2007 effects of the aspartame metabolite methanol on organs/tissues/cells and function of the immune system were described, these observations are considered more likely to result from an indirect stress-effect due to the high methanol levels used, in addition these high dose levels are not considered relevant for aspartame exposure. In addition, the quality of the studies was poor.…”
Section: Resultsmentioning
confidence: 99%
“…The study not considered relevant for evaluation of possible immunotoxicity of aspartame and its quality is poor. Parthasarathy et al (2006Parthasarathy et al ( , 2007 studied the in vivo effects of methanol, a known metabolite of aspartame in male rats at levels of 2.37 g/kg bw/day administered intraperitoneally for 1, 15 and 30 days (minimal lethal dose of methanol is 9.5 g/kg bw/day in rats). In their first study (2006) they reported that methanol intoxication resulted in effects on the antioxidant status, lipid peroxidation and DNA integrity in the hypothalamic-pituitary-adrenal axis.…”
Section: The Authors Concluded That Formaldehyde From Concentrations mentioning
confidence: 99%
See 1 more Smart Citation
“…MeOH has been recognized as an important neurotoxicant in humans in which its toxicity is manifested at lower doses than ethanol (Sandhir and Kaur, 2006). MeOH is widely used in manufacturing, biological research, household and cleaning business and undergoes one of the highest releases to the environment based on its mixability with water and organic fluid (Mellerick and Liu, 2004; Parthasarathy et al, 2007). Methanol is biologically produced during the hydrolysis ofmethyl esters, fermentation and the combustion of green plants; it generates very reactive formaldehyde and formic acid that are well known as in vitro and in vivo toxicants (Seme et al, 1999; Treichel et al, 2003).…”
Section: Introductionmentioning
confidence: 99%